Discovering the Presence of Fathers: A Study on Fathers’ Involvement in Childcare in Madiun Residency - Evi Muafiah; Anis Afifah; Lutfiana Dwi Mayasari; Ahmad Mujib (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
The evolving understanding of fatherhood has drawn increasing scholarly attention to paternal involvement as a key dimension of child development. In Indonesia, cultural expectations and economic pressures often restrict fathers’ direct participation in daily childcare, raising questions about how they negotiate their presence and involvement under such conditions. This study explores the nature of father involvement in the Madiun Residency, addressing the gap in understanding how limited physical time may be balanced by the quality of interaction. Using a mixed-methods design, quantitative data on the amount of daily father–child interaction were combined with qualitative interviews exploring fathers’ perceptions, emotional engagement, and caregiving styles. The analysis examined how time and quality relate to children’s developmental outcomes. The findings indicate that while physical interaction time is relatively limited, quality engagement plays a crucial role in supporting emotional and social development, whereas physical development correlates more directly with time spent together. Three typologies of fathering have been identified: permissive, democratic, and democratic–permissive. Each typology represents a distinct approach to paternal involvement and responsiveness, particularly within the constraints of time. The study concludes that effective paternal involvement in contemporary Indonesian families extends beyond the dimension of duration and is better understood through the quality, emotional resonance, and intentionality of fathers’ interactions with their children. These insights have practical implications for family education and policy initiatives aimed at strengthening meaningful father–child relationships.